Helmets and mouth guards: The role of personal equipment in preventing sport-related concussions - Daneshvar, D. H.; Baugh, C. M.; Nowinski, C. J.; McKee, A. C.; Stern, R. A.; Cantu, R. C. (Clinics in Sports Medicine, 2011)
Millions of athletes in the United States experience concussions annually. Although helmets and mouth guards have decreased the risk of catastrophic head injuries, their protective effects on concussions are less clear. This article evaluates the current literature on the effect of equipment on concussions. Understanding the role that these equipment play in preventing concussions is complicated by many factors, such as selection bias in nonrandomized studies, variations in playing style, and risk compensation in sports with mandatory protective equipment. Improving coach and player education about proper concussion management, encouraging neck-strengthening exercises, and minimizing high-risk impacts may reduce concussions in sports.